Utilizing fuzzy logic controller in manufacturing facilities design: Machine and operator allocation. Issue 1 (1st January 2020) - Tashtoush, Tariq; Alazzam, Azmi; Rodan, Ali
Abstract: In this paper, a fuzzy logic controller will be introduced and discussed that can be applied for manufacturing systems. Our proposed control system will utilize fuzzy logic principles to find the optimum number of machines and operators assignment by developing the heuristic relations between the inputs and the outputs of the controller. The project inputs are the desired daily production and the average product processing time by each machine. The production process is assumed to be automated and the routing of products to these machines will be automated and requires negligible time. All machines are also assumed identical in both the functionality (manufacturing process) and the service time. Given the inputs as the number of products and the average service time, the goal of this controller will be to determine the number of the machines and the number of the operators needed to meet the production demand.